Pengaruh Model Pembelajaran Concept Sentence Terhadap Keterampilan Menulis Teks Fabel Siswa Kelas VII SMP Negeri 1 Tanah Pinem Tahun Ajaran 2022/2023 - Triana Ayuningsih Ujung; Rosmaini Rosmaini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This study aims (1) to analyze the skills of writing fable texts for class VII students of SMP Negeri 1 Tanah Pinem for the 2022/2023 academic year using the conventional learning model; (2) To analyze the skills of writing fable texts for class VII students of SMP Negeri 1 Tanah Pinem for the 2022/2023 Academic Year using the Concept Sentence learning model; (3) To analyze the effect of the Concept Sentence learning model in improving the skills of writing fable texts for class VII students of SMP Negeri 1 Tanah Pinem Academic Year 2022/2023. The method used in this research is the experimental method of two group post-test design. The population in this study were all students of class VII SMP Negeri 1 Tanah Pinem. The population of class VII students at SMP Negeri 1 Tanah Pinem for the 2022/2023 academic year is 108 students divided into 4 classes. Of the 108 students, the samples in this study were class VII-A which consisted of 27 students and class VII-C which consisted of 27 students. In this study, the researcher made class VII-A as the experimental class, while class VII-C was the control class. The data analysis technique used in this study is quantitative data by using analysis requirements test, homogeneity test, and hypothesis testing. The results showed that the average value of the fable text writing skills of the experimental class students was 83.96 belonging to the good category while the average value of the control class was 62.25 belonging to the sufficient category and did not meet the Minimum Completeness Criteria (KKM), namely 75. Based on the t test, the significance level value α = 0.05 and n = 27 is obtained, ttable = 2.056. Thus it can be concluded that tcount > ttable, that is, 8.68 > 2.056, so the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This proves that there is a significant effect of using the Concept Sentence learning model on the skills of writing fable texts for class VII students of SMP Negeri 1 Tanah Pinem for the 2022/2023 academic year.